Growth and dichroic properties of LiBa12(BO3)7F4 crystal. Issue 9 (4th August 2016) - Kokh, A.; Simonova, E.; Maillard, A.; Maillard, R.; Svetlichnyi, V.; Andreev, Yu.; Kragzhda, A.; Kuznetsov, A.; Kokh, K.
Abstract : LiBa12 (BO3 )7 F4 crystal grown from BaCO3 :BaF2 :H3 BO3 :Li2 CO3 =3:3:3:1 melt was found to have a distinct linear dichroism effect at 0.35‐0.65 and around 0.73 μm. This suggests application of the material in the production of polarizing filters and attenuators for visible range lasers . Abstract : The bulk crystals of LiBa12 (BO3 )7 F4 were obtained from two flux compositions by the top seeded solution growth method. Crystals grown from BaCO3 :BaF2 :H3 BO3 :Li2 CO3 = 3:3:3:1 charge were found to have a distinct linear dichroism effect at 0.35–0.65 and around 0.73 μm. This suggests application of the material in the production of polarizing filters and attenuators for visible range lasers.